Recovering 3D shape and motion from image streams using nonlinear least squares - Szeliski, Rick; Kang, Sing Bing (Journal of Visual Communication and Image Representation, 1994)
Abstract The simultaneous recovery of 3D shape and motion from image sequences is one of the more difficult problems in computer vision. Classical approaches to the problem rely on using algebraic techniques to solve for these unknowns given two or more images. More recently, a batch analysis of image streams (the temporal tracks of distinguishable image features) under orthography has resulted in highly accurate reconstructions. We generalize this approach to perspective projection and partial or uncertain tracks by using a nonlinear least squares technique. While our approach requires iteration, it quickly converges to the desired optimal solution, even in the absence of a priori knowledge about the shape or motion. Important features of the algorithm include its ability to handle partial point tracks, to use line segment matches and point matches simultaneously, and to use an object-centered representation for faster and more accurate structure and motion recovery. We also discuss how a projective (as opposed to scaled rigid) structure can be recovered when the camera calibration parameters are unknown.